Adoption of rapid diagnostic tests for the diagnosis of malaria, a preliminary analysis of the Global Fund program data, 2005 to 2010. - Jinkou Zhao (Public Library of Science (PLoS), 2012)
Introduction The World Health Organization Guidelines for the Treatment of Malaria, in 2006 and 2010, recommend parasitological confirmation of malaria before commencing treatment. Although microscopy has been the mainstay of malaria diagnostics, the magnitude of diagnostic scale up required to follow the Guidelines suggests that rapid diagnostic tests (RDTs) will be a large component. This study analyzes the adoption of rapid diagnostic testing in malaria programs supported by the Global Fund to fight AIDS, Tuberculosis and Malaria (Global Fund), the leading international funder of malaria control globally. Methods and findings We analyzed, for the period 2005 to 2010, Global Fund programmatic data for 81 countries on the quantity of RDTs planned; actual quantities of RDTs and artemisinin-based combination treatments (ACTs) procured in 2009 and 2010; RDT-related activities including RDTs distributed, RDTs used, total diagnostic tests including RDTs and microscopy performed, health facilities equipped with RDTs; personnel trained to perform rapid diagnostic malaria test; and grant budgets allocated to malaria diagnosis. In 2010, diagnosis accounted for 5.2% of malaria grant budget. From 2005 to 2010, the procurement plans include148 million RDTs through 96 malaria grants in 81 countries. Around 115 million parasitological tests, including RDTs, had reportedly been performed from 2005 to 2010. Over this period, 123,132 health facilities were equipped with RDTs and 137,140 health personnel had been trained to perform RDT examinations. In 2009 and 2010, 41 million RDTs and 136 million ACTs were purchased. The ratio of procured RDTs to ACTs was 0.26 in 2009 and 0.34 in 2010. Conclusions/significance Global Fund financing has enabled 81 malaria-endemic countries to adopt WHO guidelines by investing in RDTs for malaria diagnosis, thereby helping improve case management of acute febrile illness in children. However, roll-out of parasitological diagnosis lags behind the roll-out of ACT-based treatment, and will require prioritization of investments.